Finite-Time Distributed Filtering of Time-Varying Switched Stochastic Systems With DoS Attacks Based on Encoding-Decoding Scheme - Fu, Hua; Meng, Xueyang; Chen, Yun (IEEE systems journal, 2024)
This article is devoted to the finite-time distributed H_{∞ } filtering problem for a class of time-varying switched stochastic systems subject to denial-of-service (DoS) attacks over sensor networks. To fully utilize the limited network resources, an encoding-decoding scheme is introduced to facilitate the data transmissions through the sensor-to-filter channels. The Bernoulli random variables are utilized to characterize the DoS attacks occurring in a random way. The purpose of the tackled problem is to design a desired distributed filtering method such that both the stochastic finite-time boundedness and prescribed stochastic H_{∞ } performance are achieved for the resultant filtering error dynamics. On the basis of stochastic analysis method and average dwell time technique, the sufficient conditions are established to guarantee the existence of the desired filter for each node, and then, the proper filter parameters are calculated by solving a set of iterative matrix inequalities. Subsequently, a recursive distributed filtering algorithm is put forward that is suitable for online implementation. Finally, the validity of the obtained theoretical results is demonstrated by a numerical example.